Exacerbations of Chronic Rhinosinusitis—Microbiology and Perspectives of Phage Therapy - Szaleniec, Joanna (Antibiotics (Basel), 2019)
The chronically inflamed mucosa in patients with chronic rhinosinusitis (CRS) can additionally be infected by bacteria, which results in an acute exacerbation of the disease (AECRS). Currently, AECRS is universally treated with antibiotics following the guidelines for acute bacterial rhinosinusitis (ABRS), as our understanding of its microbiology is insufficient to establish specific treatment recommendations. Unfortunately, antibiotics frequently fail to control the symptoms of AECRS due to biofilm formation, disruption of the natural microbiota, and arising antibiotic resistance. These issues can potentially be addressed by phage therapy. In this study, the endoscopically-guided cultures were postoperatively obtained from 50 patients in order to explore the microbiology of AECRS, evaluate options for antibiotic treatment, and, most importantly, assess a possibility of efficient phage therapy. Staphylococcus aureus and coagulase-negative staphylococci were the most frequently isolated bacteria, followed by Haemophilus influenzae, Pseudomonas aeruginosa, and Enterobacteriaceae. Alarmingly, mechanisms of antibiotic resistance were detected in the isolates from 46% of the patients. Bacteria not sensitive to amoxicillin were carried by 28% of the patients. The lowest rates of resistance were noted for fluoroquinolones and aminoglycosides. Fortunately, 60% of the patients carried bacterial strains that were sensitive to bacteriophages from the Biophage Pharma collection and 81% of the antibiotic-resistant strains turned out to be sensitive to bacteriophages. The results showed that microbiology of AECRS is distinct from ABRS and amoxicillin should not be the antibiotic of first choice. Currently available bacteriophages could be used instead of antibiotics or as an adjunct to antibiotics in the majority of patients with AECRS.